(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Ichnocarpus frutescens has a broad spectrum in the indigenous system of medicine. It is commonly known as the black creeper belonging to the family of apocynaceae. The present study investigates the physicochemical and phytochemical characteristics of three different extracts of leaves of Ichnocarpus frutescens by using standard methods. The phytochemical evaluation included colour and consistency, fluorescent behaviour and qualitative analysis. The Physicochemical screening determined extractive value, ash value and moisture content. Results revealed the presence of carbohydrates, glycosides, flavonoids, phytosterols and phenolic compounds. This study of Ichnocarpus frutescens will help in quality analysis of crude drug and lay down the standards which can be useful in future experimental studies.